SWOT Analysis as a Strategic Approach in Improving Education Quality - Saeful Anwar; Iskandar Sulaeman (Universitas Islam Nusantara, Bandung, 2025)
SWOT analysis is an effective approach to planning educational quality improvement. This study analyzes the strengths, weaknesses, opportunities, and threats faced by MIN Bandung. The research method used a qualitative approach and method so that the researcher could present the findings descriptively. The data sources used in this study include all data sources covering documents, recordings, archives, interview results, direct observations, participant observations, and physical devices such as videos and images. Meanwhile, the data used in the study consists of two types, namely: (1) primary data; and (2) secondary data. The results of this study, namely the SWOT analysis, provide a comprehensive view of the factors that influence the quality of education at MIN Bandung. Through the identification of strengths, weaknesses, opportunities, and threats, schools can develop appropriate strategic plans to improve the quality of education. It is important to utilize existing strengths, overcome weaknesses, take advantage of opportunities, and face threats with appropriate actions. The strategic plan must involve all stakeholders, including teachers, administrative staff, students, parents, and external partners. Through regular monitoring and evaluation, the school can measure progress and make adjustments if necessary.